Cuidados paliativos à criança com câncer no contexto hospitalar: percepção de enfermeiros à luz da teoria de Jean Watson - Dias, Thainá Karoline Costa (2022)
Introduction: Palliative care in pediatric oncology is defined by the comprehensive care provided by a multidisciplinary team, which aims to provide physical, spiritual, mental and social support to these individuals, also covering the needs of their families. Therefore, it is essential for nurses to participate as a member of the palliative team in promoting the well-being of children with cancer, at any stage of their treatment. In this sense, the nursing theory focused on human care, developed by Jean Watson, is of great importance, since it supports and guides the assistance of these professionals through its proposed elements, in order to facilitate the transpersonal relationship of nurses with their patients. Objective: To understand nurses' assistance to children with cancer in palliative care in the light of Jean Watson's Theory. Method: This is an exploratory study with a qualitative approach, based on the Theory of Jean Watson, which was carried out in a hospital in the municipality of João Pessoa - Paraíba, Brazil, a reference in the treatment of the population affected by cancer in different age groups. , where we worked with ten nurses who provide targeted care to children affected by cancer in palliative care, through a recorded interview. The collection of empirical material took place between October and December 2020, using the semi-structured interview technique. The empirical material was analyzed using the content analysis technique. The research project was approved by a Research Ethics Committee at the Federal University of Paraíba, on October 22, 2020, under protocol nº 4,354,631. Results: From the analysis of the empirical material, it was observed that the testimonies of the nurses interviewed emphatically reflect on the knowledge in the field of care for children with cancer in palliative care, since the strategies implemented in this scenario by the study participants are coherent with Jean Watson's Theory, based on the elements contained in the Clinical Caritas Process. Final thoughts: Nurses seek to offer a humanized and comprehensive care that meets the child with cancer in palliative care in all its biopsychosocial-spiritual dimensions, basing their practice on humanistic factors and scientific knowledge, in line with Jean Watson's Theory, with the scope in promoting comfort and pain relief, through playful, dialogic, creative, loving and transpersonal practices. Thus, the evidence contributes to the advancement of knowledge and clinical nursing practice in the field of palliative care in pediatric oncology.